Languishing in 'rent-a-Marx/Margaret rhetoric': the phono-politics of Douglas Oliver's The Infant and the Pearl. Issue 8 (2nd August 2020) - Farmer, Gareth
ABSTRACT: In The Infant and the Pearl (1985), the poet Douglas Oliver draws on the alliterative and allegorical features of mediaeval verse to create a dream-like satire of Britain under Margaret Thatcher. Once a central feature of most Old English poetry, since Chaucer, alliteration and rhyme have often been used in the service of parody and satire. But, how do complex sound-structures aid satire and generate political content? Drawing on Oliver's poetic and critical work, as well as contemporary research into prosody and politics, this article argues that the sound patterning in The Infant and the Pearl creates a caricatured version of Thatcher's 'politically unsound' Britain. Oliver uses sonic patterns to create an artificial parody of the bathetic 'uncommon rhetoric' of consumerism and the 'false pearls' of the political classes. Far from being an accessory to meaning, the sound structures are vehicles for parodying the operations of the rhetoric of the 'unreal' apparent in social and political discourse. Oliver envisages sound patterning – as performed with every private and public reading – as offering recalibrations of people's experience of language and the world, as well as leading to glimpses of a communality beyond political and social division.